2012
DOI: 10.3126/njog.v6i2.6755
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antenatal Care on Maternal and Perinatal utcome: A Study at Nepal Medical College Teaching Hospital

Abstract: NJOG 2011 Nov-Dec; 6 (2): 37-43 Aims: To identify the determinants of antenatal care (ANC) attendance and its impact on maternal / perinatal outcome.Methods: Prospective descriptive study of women delivered at Nepal Medical College Teaching Hospital (NMCTH), a 700 bedded tertiary care hospital situated at periphery of Kathmandu.Results: Among 322 women delivered during period of four months, majority (87%) reported of attending more than 4 antenatal visits, only 21 (6.5%) women had not attended ANC. The most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 0 publications
9
51
4
Order By: Relevance
“…In a Study conducted in Kathmandu it was found that peri natal mortality was 16 times higher among no ANC or inadequate ANC than that in the group with more than 4 visits. 9 An analysis of District Level Household Survey (2007-2008) conducted in India too revealed results similar to present study. 10 In our research, we put assisted delivery and Caesarian section together and tried to find out the association between modes of delivery and neonatal death.…”
Section: Discussionsupporting
confidence: 72%
“…In a Study conducted in Kathmandu it was found that peri natal mortality was 16 times higher among no ANC or inadequate ANC than that in the group with more than 4 visits. 9 An analysis of District Level Household Survey (2007-2008) conducted in India too revealed results similar to present study. 10 In our research, we put assisted delivery and Caesarian section together and tried to find out the association between modes of delivery and neonatal death.…”
Section: Discussionsupporting
confidence: 72%
“…228 (75.8%) started to attend ANC only in 2 nd trimester and only 66 (21.9%) had started from 1 st trimester. 11 In the study conducted by Dasgupta Urmila et al on ante natal care utilization from a metropolitan city revealed that 36.5% of mothers had done ante natal registration in first trimester which is similar to our study. 9 Registration of pregnancy is essential to provide the effective care & follow up care of the mother.…”
Section: Resultssupporting
confidence: 90%
“…This finding appeared to be lower than studies done in Ethiopia (Eastern Hararghe zone 38.3% [13] and Holeta town 66% [14]) and abroad Kenya 52% [15], Nigeria 81.5% [16] and Nepal 87% [17]. The probable reason for this might be due to availability of private quality service providing health facilities and also availability of approachable healthcare providers.…”
Section: Discussionmentioning
confidence: 67%